A genetic screen pinpoints ribonucleotide reductase residues that sustain dNTP homeostasis and specifies a highly mutagenic type of dNTP imbalance - Schmidt, Tobias Thomas; Wade, Rebecca C. (Nucleic acids research, 2019)
Abstract. The balance and the overall concentration of intracellular deoxyribonucleoside triphosphates (dNTPs) are important determinants of faithful DNA repli